Genome of the Malawi golden cichlid fish (Melanochromis auratus) reveals exon loss of oca2 in an amelanistic morph. (12th June 2019) - Kratochwil, Claudius F.; Urban, Sabine; Meyer, Axel
Abstract: The tropical freshwater fish family Cichlidae is famous for its record‐breaking rates of speciation and diversity in colors and color patterns. Here, we sequenced the genome of the Lake Malawi cichlid Melanochromis auratus to study the genetic basis of an amelanistic morph of this species that lacks the typical melanic stripes and markings. Genome sequencing of the amelanistic and wild‐type morph revealed the loss of the second exon of the known pigmentation gene oculocutaneous albinism II ( oca2 ), also known as p(ink‐eyed dilution) gene or melanocyte‐specific transporter gene . Additional genotyping confirms the complete association with this recessive Mendelian phenotype. The deletion results in a shorter transcript, lacking an acidic di‐leucine domain that is crucial for trafficking of the Oca2 protein to melanosomes. The fact that oca2 is involved in a wide range of amelanistic morphs across vertebrates demonstrates its highly conserved function.